Protective efficient comparisons among all kinds of respirators and masks for health-care workers against respiratory viruses: A PRISMA-compliant network meta-analysis. Issue 34 (27th August 2021) - Li, Jiawen; Qiu, Yu; Zhang, Yulin; Gong, Xue; He, Yunru; Yue, Peng; Zheng, Xiaolan; Liu, Lei; Liao, Hongyu; Zhou, Kaiyu; Hua, Yimin; Li, Yifei
Abstract: Background: There is no definite conclusion about comparison of better effectiveness between N95 respirators and medical masks in preventing health-care workers (HCWs) from respiratory infectious diseases, so that conflicting results and recommendations regarding the protective effects may cause difficulties for selection and compliance of respiratory personal protective equipment use for HCWs, especially facing with pandemics of corona virus disease 2019. Methods: We systematically searched MEDLINE, Embase, PubMed, China National Knowledge Infrastructure, Wanfang, medRxiv, and Google Scholar from initiation to November 10, 2020 for randomized controlled trials, case-control studies, cohort studies, and cross-sectional studies that reported protective effects of masks or respirators for HCWs against respiratory infectious diseases. We gathered data and pooled differences in protective effects according to different types of masks, pathogens, occupations, concurrent measures, and clinical settings. The study protocol is registered with PROSPERO (registration number: 42020173279). Results: We identified 4165 articles, reviewed the full text of 66 articles selected by abstracts. Six randomized clinical trials and 26 observational studies were included finally. By 2 separate conventional meta-analyses of randomized clinical trials of common respiratory viruses and observational studies of pandemic H1N1, pooled effects show no significant difference between N95 respirators and medical masks against common respiratory viruses for laboratory-confirmed respiratory virus infection (risk ratio 0.99, 95% confidence interval [CI] 0.86–1.13, I 2 = 0.0%), clinical respiratory illness (risk ratio 0.89, 95% CI 0.45–1.09, I 2 = 83.7%, P = .002), influenza-like illness (risk ratio 0.75, 95% CI 0.54–1.05, I 2 = 0.0%), and pandemic H1N1 for laboratory-confirmed respiratory virus infection (odds ratio 0.92, 95% CI 0.49–1.70, I 2 = 0.0%, P = .967). But by network meta-analysis, N95 respirators has a significantly stronger protection for HCWs from betacoronaviruses of severe acute respiratory syndrome, middle east respiratory syndrome, and corona virus disease 2019 (odds ratio 0.43, 95% CI 0.20–0.94). Conclusions: Our results provide moderate and very-low quality evidence of no significant difference between N95 respirators and medical masks for common respiratory viruses and pandemic H1N1, respectively. And we found low quality evidence that N95 respirators had a stronger protective effectiveness for HCWs against betacoronaviruses causative diseases compared to medical masks. The evidence of comparison between N95 respirators and medical masks for corona virus disease 2019 is open to question and needs further study. Abstract : Supplemental Digital Content is available in the text